2019
DOI: 10.1007/s10096-019-03560-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with blood culture positivity in patients with complicated skin and skin structure infection—a population-based study

Abstract: Skin and skin structure infection (SSSI) is classified as complicated (cSSSI) if it involves deep subcutaneous tissue or requires surgery. Factors associated with blood culture sampling and bacteremia have not been established in patients with cSSSI. Moreover, the benefit of information acquired from positive blood culture is unknown. The aim of this study was to address these important issues. In this retrospective population-based study from two Nordic cities, a total of 460 patients with cSSSI were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The connection between alcoholism and increased risk and severity of infectious diseases, including blood culture positive infections, is well documented [ 2 , 4 , 5 , 32 , 33 ]. Prior reports have documented that alcoholics make up 7–14% of SAB patients [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The connection between alcoholism and increased risk and severity of infectious diseases, including blood culture positive infections, is well documented [ 2 , 4 , 5 , 32 , 33 ]. Prior reports have documented that alcoholics make up 7–14% of SAB patients [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholism increases the occurrence of various infectious diseases such as bacterial pneumonia and blood culture-positive infections. Furthermore, alcoholism deteriorates prognosis and increases mortality in bacterial pneumonia and blood culture-positive infections [2][3][4][5]. The connection between alcoholism and increased risk and severity of infections is presented as multifactorial [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that the rate of positivity in blood culture might be relatively low in patients with surgical site infections following spine surgery. [38][39][40] Although blood NGS is rarely used in the determination of orthopedic infections, it has already been widely used in other fields. For instance, Zhou et al 26 reported that multiorgan sepsis, including lumbar spine sepsis caused by Klebsiella pneumoniae, could be diagnosed by blood NGS.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the rate of positivity in blood culture might be relatively low in patients with surgical site infections following spine surgery. 38–40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation